Women Researching in Africa The Impact of Gender - Jackson, Ruth; Kelly, Max (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection explores the lives, consequences and motivations of female researchers in Africa, giving unprecedented insights into how their gender-and sometimes their ethnicity and age-impacted on their research experiences, and how doing research in Africa affected them as women. Each contributor considers her place or position in the research process and provides a vivid portrait of that experience. Drawing on research findings from Nigeria, Ethiopia, Cameroon, Ghana, Guinea, Malawi, Uganda and other African countries, the book looks at gender and identity as a female researcher in Africa; relationships with 'others'; and unique methodological challenges for female researchers in Africa. With refreshing candour, each chapter challenges other researchers in Africa (both women and men), to integrate critical reflections of gender and diverse gendered field experiences into their work. Women Researching in Africa will be of interest to students and scholars across a range of disciplines including development studies, anthropology, geography, gender studies and international studies.